The Use of E-games and Their Educational Implications as Viewed by Guardians of Taibah University Affiliates: A Field Study in Al-Madinah Al-Munawwarah Region - Al-Ansari, Rofaydah Adnan (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the use of e-games and its educational implications as viewed by guardians. The study adopted the descriptive approach where the study population included guardians who are working at Taibah University. The study sample consisted of 95 parents (father/mother) who were chosen by a simple random sampling method. A questionnaire was set up ensured for reliability and validity, and them was deliberately administered to parents. Many statistical methods were used to obtain the results such as frequencies, means, and standard deviation. One of the most important results of the study was the agreement of the sample members that the child’s main goal is to entertain e-games and not to obtain knowledge. It was found that the best way to spend time and enjoy it is through e-games and the child does not usually pay attention to e-games that contribute to the development of his abilities and skills. The study concluded suggesting many recommendations including studying the scientific efforts exerted in the field of technology and child culture and using them to present a scientific strategy that can be applied effectively.